1987
DOI: 10.1007/bf00166975
|View full text |Cite
|
Sign up to set email alerts
|

Muscarine receptors on the rat phrenic nerve, evidence for positive and negative muscarinic feedback mechanisms

Abstract: Neuronal transmitter stores of the rat phrenic nerve were labelled by incubation with [3H]choline. Release of [3H]acetylcholine was elicited by electrical nerve stimulation (100 or 1,500 pulses, 5 or 25 Hz) or by high potassium (27 mmol/l) and the effects of the muscarine receptor agonist oxotremorine and the antagonist scopolamine were investigated. Neither oxotremorine nor scopolamine affected the basal tritium efflux. A low concentration of oxotremorine (10 nmol/l) enhanced and a high concentration of oxotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The type of cholinoceptor sites involved in the feedback regulation however, is controversial. Muscarinic inhibitory (Duncan & Publicover, 1979;Michaelson et al, 1979;Abbs & Joseph, 1981;Somogyi et al, 1987) and excitatory (Das et al, 1978;Wali et al, 1987;Wessler et al, 1987) prejunctional cholinoceptors have been reported at vertebrate neuromuscular junctions and in the Torpedo electric organ. In the presence of tubocurarine, a frequency-dependent decrease of evoked ACh release was obtained which suggested the presence of nicotinic prejunctional cholinoceptors mediating a positive feedback control of evoked transmitter release (Glavinovic, 1979a;Magleby et al, 1981;Wessler et al, 1986;Matzner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The type of cholinoceptor sites involved in the feedback regulation however, is controversial. Muscarinic inhibitory (Duncan & Publicover, 1979;Michaelson et al, 1979;Abbs & Joseph, 1981;Somogyi et al, 1987) and excitatory (Das et al, 1978;Wali et al, 1987;Wessler et al, 1987) prejunctional cholinoceptors have been reported at vertebrate neuromuscular junctions and in the Torpedo electric organ. In the presence of tubocurarine, a frequency-dependent decrease of evoked ACh release was obtained which suggested the presence of nicotinic prejunctional cholinoceptors mediating a positive feedback control of evoked transmitter release (Glavinovic, 1979a;Magleby et al, 1981;Wessler et al, 1986;Matzner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This process starts at the endplates and advances proximally. Because it was reported that the presynaptic membrane of the motor endplate has muscarinic autoreceptors which modulate the release of acetylcholine (Wessler et al, 1987), it is conceivable that deficit of these autoreceptors causes axonal degeneration in the pmn homozygote. It is worth noting that treatment with ciliary neurotrophic factor (CNTF) prevented the degeneration of motor neuron in the pmn homozygote (Sendtner et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, electrophysiological (Beranek & Vyskocil, 1967) and histochemical data (Gillberg et al, 1984) oppose the presence of muscarinic receptors at the neuromuscular junction. Wessler et al (1987b) found that the stimulation by oxotremorine of muscarinic receptors resulted in a biphasic response: in low concentrations (10 nM) oxotremorine enhanced whereas in higher concentrations (1 pM) it inhibited the release of ACh. These data and our earlier observations that oxotremorine reduces the release of ACh (Vizi et al, 1985; suggest that the release of ACh from the neuromuscular junction is modulated by muscarinic receptors.…”
Section: Stimulationmentioning
confidence: 99%
“…However, it has been shown that the muscarinic receptor agonist oxotremorine reduced , and the antagonist atropine enhanced Wessler et al, 1987b) the release of ACh evoked by electrical stimulation. This suggests that negative feedback modulation mediated via muscarinic receptors occurs at the neuromuscular junction Wessler et al, 1987b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation